Marketing Social Innovation Products with IMC - Dwinanto Kurniawan; Nafiah Ariani (LPPM Stikosa - AWS, 2022)
Cumin tea is an herbal product with myriad of benefits. This tea is produced in Tinumpuk Village, Indramayu Regency. Community-based organization that produces this tea belongs to the Ikatan Mantan Buruh Migran–Desa Tinumpuk (IBU TIN). This study aims to determine the application of integrated marketing communication by CBO IBU TIN, especially in marketing cumin tea. This research uses qualitative approach and case study method. The techniques used to collect data are observation, in-depth interviews, and documentation studies. Data analysis technique used Miles & Huberman interactive analysis, while triangulation of data sources was used to test the validity of the data. The results of the study shows that marketing of cumin tea products by CBO IBU TIN has used several elements in integrated marketing communication, namely advertising, sales promotion, personal selling, public relations, event marketing, and packaging. This finding also shows that CBO IBU TIN does not use digital (interactive) communication in marketing the cumin tea products. Keywords: Integrated Marketing Communication, Migrant Workers, Cumin Tea